Participation Analysis of Class IV A Female Students in Learning at SD Kemala Bhayangkari 10 Porong: Analisis Partisipasi Siswa Perempuan Kelas IV A dalam Pembelajaran SD Kemala Bhayangkari 10 Porong - Fiddaroyni, Finny; Wachidah, Kemil (Indonesian Journal of Education Methods Development, 2020)
This study aims to describe the participation of female students at IV A SD Kemala Bhayangkari 10 Porong. This research is a qualitative critical research. The subject of this study was fourth grade students of SD Kemala Bhayangkari 10 Porong. Data collection techniques using observation, interviews, and documentation. The data analysis in this study uses domain analysis, compound analysis, taxonomy analysis and theme analysis. Data validity techniques using technical triangulation. The results showed that the participation of female students in grade IV A SD Kemala Bhayangkari 10 Porong was low. Internal factors that influence the low participation of female students in grade IV A are psycological factors, namely the interest of female students based on the attitude of subjects. External factors that influence the low participation of female students in grade IV A are school factors, namely the stereotype of male students towards female students’ intellectual and symbolic violence in the relationship between teacher and child.